Cross-cultural Comparison of Consumption Perceptions of Luxury Brands amongst American and Chinese Young Consumer - ZHU, Meiyi (2013)
The global luxury markets have been fast developed in the past twenty-five years, in which the market in the United States and China are the two biggest ones. This study mainly examined influencing factors that affect Chinese and American young consumers’ perceptions towards luxury brands and further explore how cultural differences influence their perceptions. Data was collected both in China and America, and overall 16 interviewees were involved. By using a qualitative method and interpretive analyses, the results highlighted that Chinese young people lay much emphasis on social-oriented perceptions, while Americans tend to show more personal-oriented perceptions than Chinese, especially showing high inner-self to others. In addition, three cultural dimensions - individualism vs. collectivism, power distance, and long-term vs. short-term orientation - have an impact on their perceptions of luxury brands. Managerial implications are further discussed in the end.